DOP077 Deep immunophenotyping reveals a role for Mucosal Associated Invariant T (MAIT) cells in the response to anti-TNF treatment in Crohn's disease. (16th January 2018) - Walshe, M; Elliott, L A; Danso-Abeam, D; Cullen, G; Sheridan, J; Mulcahy, H; Ryan, E; Doherty, G
Abstract: Background: Aberrations in various immune cell subsets have been identified in Crohn's disease. However, most studies focus on a single type of immune cell in isolation, limiting our understanding of how cellular and humoural immune systems interact. In addition, heterogeneity of immune-phenotypes may explain variation in treatment response. We examined differences in immune-cell subsets in patients with Crohn's disease commencing anti-TNF treatment. Methods: Patients with Crohn's disease commencing infliximab or adalimumab were recruited prospectively in the outpatient setting. Age-matched healthy controls were recruited contemporaneously with each patient. Demographic and clinical data including disease phenotype, CRP, calprotectin, and HBI were recorded. Blood samples were obtained from patients and matched controls at week 0, 2, and 14 (approx.) of treatment. Patients were deemed responders or non-responders at week 14 based on a composite of clinical scores, biomarkers, and need to escalate treatment. Flow cytometry using four panels comprising a total of 34 antibodies was used to analyse approximately 30 different cell types including B cells, T cells, and antigen-presenting cells (monocytes and dendritic cells). PRISM software was used for statistical analysis. Results: Baseline comparison of 19 CD patients (Table 1) and controls shows multiple differences. Patients have a significantly lower frequency of MAIT (CD3+CD161++Vα7.2+) cells and non-classical monocytes (HLA-DR+CD14−CD16+). Patients also show a higher frequency of naïve (CD19+IgD+27−) B cells, and lower frequency of class-switched memory (CD19+IgD−CD27+) B cells ( p < 0.05). 13 patients have reached the week 14 timepoint, enabling determination of treatment response. 8/13 (62%) patients are deemed responders. Baseline MAIT cell frequencies are strikingly lower in responders vs. non-responders ( p < 0.05). Treatment with anti-TNF does not alter frequencies of MAIT cells, non-classical monocytes, naïve B cells, or class-switched memory B cells over a 14-week treatment period. Conclusions: Many immune cell subsets are perturbed in Crohn's disease. However, only MAIT cell frequency was associated with response to anti-TNF. A low MAIT cell count in peripheral blood may signify TNF-predominant inflammatory response. This novel association between immune-phenotype and treatment response may aid patient-tailored treatment in the future.